PENGARUH GUIDED IMAGERY TERHADAP TEKANAN DARAH PADA MASYARAKAT DENGAN HIPERTENSI - Mantiri, Sintha; Wantania, Frans Erwin Nicolaas; Nurmansyah, Muhamad (Universitas Sam Ratulangi, 2024)
Background: Hypertension is a chronic disease that cannot be cured but must be controlled through various therapeutic efforts both pharmacological therapy and nonpharmacological therapy. One of the nonpharmacological therapies that can provide a relaxing effect on the body to be able to control blood pressure is guided imagery therapy. Objective: This study aims to identify the effect of Guided Imagery therapy on changes in blood pressure in people with hypertension. Methods: This study is a type of quantitative research that uses pre experimental research methods with One group pre-test and post-test design, namely measuring blood pressure using a tensimeter before being given an intervention and after being given an intervention. The sample size was 21 people with hypertension who were taken using non probability sampling technique using consecutive sampling. Results: After the intervention there was a decrease in mean systolic blood pressure by 20 mmHg and diastolic blood pressure by 10 mmHg. The results of the Wilcoxon Signed Rank test analysis in this study showed that there was a difference in systole blood pressure before guided imagery intervention and after intervention with a P value (0.000), and a difference in diastole blood pressure before guided imagery intervention and after intervention with a P value (0.000). Conclusion: Based on the results of the research conducted, it was found that there was an effect of guided imagery on blood pressure in people with hypertension in Kali village, Pineleng sub-district, so it is hoped that people can do guided imagery independently and routinely as an effort to control blood pressure Keywords: guided imagery; hypertension; blood pressure